(Non)retroflexivity of Slavic affricates and its motivation: evidence from Polish and Czech - Żygis, Marzena (ZAS Papers in Linguistics, 2005)
The goal of this paper is two-fold. First, it revises the common assumption that the affricate <č> denotes /t͡ʃ/ for all Slavic languages. On the basis of experimental results it is shown that Slavic <č> stands for two sounds: /t͡ʃ/ as e.g. in Czech and /ʈʂ/ as in Polish.The second goal of the paper is to show that this difference is not accidental but it is motivated by perceptual relations among sibilants. In Polish, /t͡ʃ/ changed to /ʈʂ/ thus lowering its sibilant tonality and creating a better perceptual distance to /tɕ/, whereas in Czech /t͡ʃ/ did not turn to /ʈʂ/, as the former displayed sufficient perceptual distance to the only affricate present in the inventory, namely, the alveolar /t͡s/. Finally, an analysis of Czech and Polish affricate inventories is offered.